Mitigation vs. adaptation: A critical overview of EU climate change policies and their impact on agriculture - Cosmin Boiangiu Marius (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 8th Edition of the International Symposium, November 2017, Bucharest, 2017)
The paper does a qualitative assessment of the current European Union policies for dealing with climate change. In the EU mitigation policies are derived from the international agreementsforreducing and limiting greenhouse gases emissions. Mitigation policies have a strict compliance regime using both positive and negative reinforcement. On the other side, adaptation measures, meant to increase nature's and society's resilience to climate change negative impact, are designed more as recommendations complementing sectoral policies. Agriculture has a relatively low potential of curbing GHG emissions but are some of the most vulnerable sectors to climate change. By examining the relative projected efficiency of EU's mitigation efforts compared to the overall goal of stopping global warming, the paper finds that there is clear imbalance between mitigation policies and adaptation policies. It concludes that in the absence of matching binding commitments from other large emitters of GHG, the climate objective will not be met. This requires at European level a medium and long-term strategy for the societal and economic adaptation to the new climate conditions and, on short-term, more focus on adaptation policies in vulnerable sectors such as agriculture.
Keywords: O38; Q01; 330; Climate change policies; European Union; mitigation; adaptation; agriculture